Essentials of intellectual disability assessment and identification - Brue, Alan W.; Wilmshurst, Linda (New Jersey : Wiley, 2016)
A concise, up-to-date overview of intellectual disability evaluation and assessment Essentials of Intellectual Disability Assessment and Identification offers a practical, concise overview of the nature of intellectual disability and adaptive skills functioning in children, adolescents, and adults. Coverage includes the latest information on prevalence, causes, differential diagnoses, behavioral and social.
Includes bibliographical references and index.
Keywords: Developmental disabilities; Intelligence tests; Educational tests and measurements